2021
DOI: 10.13057/biodiv/d220147
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of medicinal plants used for maintaining stamina in Madura ethnic, East Java, Indonesia

Abstract: Abstract. Fathir A, Haikal M, Wahyudi D. 2021. Ethnobotanical study of medicinal plants used for maintaining stamina in Madura ethnic, East Java, Indonesia. Biodiversitas 22: 386-392. The use of herbal medicine that expands rapidly across the world opens a lot of opportunities for drug exploration and discovery through ethnobotanical study. Therefore, countries with high level of biological and cultural diversity like Indonesia have great opportunities to achieve this goal, and even Indonesia has its own term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The most frequent was oral ingestion (Figure 3C). This is similar to previous studies (Nguyen et al 2019;Fathir et al 2021). Allium cepa was discovered to be inhaled to treat colds.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The most frequent was oral ingestion (Figure 3C). This is similar to previous studies (Nguyen et al 2019;Fathir et al 2021). Allium cepa was discovered to be inhaled to treat colds.…”
Section: Discussionsupporting
confidence: 91%
“…Figure 3A shows that leaves were the most common plant material used in Minasatene (Bantimurung-Bulusaraung National Park). Leaves are the major plant component commonly used in herbal medicine in Indonesia (Mustofa et al 2020;Fathir et al 2021) and other countries (Chaachouay et al 2020;Islam et al 2020), as this part can be easily found in tropical regions. It's also known to be easy to handle and more sustainable compared to other parts of plants in terms of preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Jamu as herbal medications are widely practiced in many communities living in the islands of the Indonesian archipelago, spreading from the main islands of Sumatra [27-29], Java and Madura [30][31][32][33], Kalimantan [34][35][36], Sulawesi [37][38][39], Papua [40,41], as well as their smaller neighboring islands. Traditionally Jamu is prepared from raw herbal ingredients in two methods, i.e.…”
Section: Indonesian Herbal Medicine and Possible Adulterantsmentioning
confidence: 99%
“…In the families of Musaceae, Piperaceae, Fabaceae, and Asteraceae were only found four species each. Furthermore, plant species from Fabaceae or Asteraceae were also widely used as drugs and stamina boosters, as seen in the Tunjung Dayak community in East Kalimantan (Setyowati 2010), Lampung Saibatin (Wakhidah 2020), and Madura (Fathir et al 2021). Kedawung (Parkia timoriana (DC.)…”
Section: The Use Of Medicinal Plantsmentioning
confidence: 99%